Micro‐Light‐Emitting Diodes Based on InGaN Materials with Quantum Dots. Issue 6 (29th December 2021) - Liu, Zhaojun; Hyun, Byung‐Ryool; Sheng, Yujia; Lin, Chun‐Jung; Changhu, Mengyuan; Lin, Yonghong; Ho, Chih‐Hsiang; He, Jr‐Hau; Kuo, Hao‐Chung
Abstract: Micro‐light‐emitting diodes (Micro‐LEDs) based on gallium nitride (GaN) materials offer versatile platforms for various applications, including displays, data communication tools, photodetectors, and sensors. In particular, the introduction of Micro‐LEDs in the optoelectronic industry enables the development of novel short‐distance wireless communication applications for the Internet of Things as well as near‐to‐eye displays for virtual reality and augmented reality. Micro‐LEDs used in conjunction with colloidal quantum dots (QDs) as color‐conversion layers provide efficient full‐color displays as well as white LEDs for high‐speed visible light communications (VLCs). Here, the latest progress on full‐color Micro‐LED displays with a printed QD color conversion layer, GaN material‐based Micro‐LEDs for VLC systems, and the photostability of novel QD materials for Micro‐LEDs is comprehensively reviewed. Outlooks on the efficiency of Micro‐LEDs with sizes ≤10 µm, QD stability issues, and flexible Micro‐LED displays are also provided. Abstract : Micro‐light‐emitting diodes (Micro‐LEDs) based on indium gallium nitride and gallium nitride hold tremendous potential for various applications. The latest progress on Micro‐LEDs with printing quantum dot (QD) conversion layers, novel QD materials and visible light communications systems are comprehensively summarized in this review along with challenges and opportunities.